Modulation of Infectious Salmon Anaemia Virus Infection by Clathrin-Mediated Endocytosis and Macropinocytosis Inhibitors - Vasquez-Martinez, y; Cortez-San Martin, M; Galleguillos-Becerra, C; Michelson-Quintana, S (Elsevier B.V., 2024)
Infectious salmon anaemia virus (ISAV) is a pathogen that causes disease and large mortality in farm-raised Salmo salar L., being considered as a major problem in the salmon industry. However, despite its relevance, there are still numerous knowledge gaps on virus entry and early stages of infection. Previous studies suggested that virus entry into cells occurs via endocytosis, with no description of specific mechanisms. However, it remains unknown if the endocytosis induced by ISAV is a clathrin-dependent or clathrin-independent process. This study aimed to identify cellular mechanisms allowing ISAV entry into Atlantic Salmon head kidney (ASK) cells. Our results showed that ISAV can be found in coated pits and membrane ruffles, the latter being induced by a rearrangement of actin filaments promoted by ISAV infection. Additionally, it was determined that ISAV stimulate the uptake of extracellular fluid in a multiplicity of infection (MOI)-dependent manner. When the clathrin-mediated endocytic pathway was pharmacologically inhibited, ISAV infection was significantly reduced but not entirely inhibited. Similarly, when the Na+/H+ exchanger (NHE), a key component of macropinocytosis, was inhibited, ISAV infection was negatively affected. Our results suggest that ISAV enters cells via both clathrin-mediated endocytosis and most likely macropinocytosis. © 2023